IMPLEMENTASI PEMBELAJARAN MATEMATIKA BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) DI MI SAINS AL-HIDAYAH KOTA SORONG - Rahmatia Dwi Ciptarani; Rusdin Rusdin; Agus Yudiawan (MISOOL: Jurnal Pendidikan Dasar, 2021)
This study aims to describe how the implementation of HOTS-based learning in mathematics subjects at MI Sains Al-Hidayah Sorong City includes planning, implementation, and learning assessment. This research is a qualitative type with a descriptive approach. Researchers conducted in-depth observations in class IV. The data were obtained from the learning implementation plan document, interviews, and direct observation during the learning process. Data is presented and analyzed through the process of data reduction, presentation, and drawing conclusions. Checking the validity of the data is done by triangulation of sources to mathematics teachers, madrasa principals, and supervisors. The results of the study show that learning planning is carried out by making lesson plans that contain HOTS-based activities. The learning process is also applied with problem-solving discussions to work on HOTS-based questions. Assessment is carried out at each meeting through practice questions, daily tests, UTS, and UAS.